2018
DOI: 10.1149/2.0431805jes
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microstructure and Surface Finish on the Corrosion of Selective Laser Melted 304L

Abstract: The corrosion behavior of selective laser melted (SLM) 304L was investigated and compared to conventional wrought 304L in aqueous chloride and acidic solutions. Through immersed electrochemical testing and exposure in acidic solutions, the SLM 304L exhibited superior pitting resistance in the polished state compared to wrought 304L. However, the surface condition of the SLM material had a great impact on its corrosion resistance, with the grit-blasted condition exhibiting severely diminished pitting resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 45 publications
4
40
0
Order By: Relevance
“…10b, c, which was also confirmed by other reports. 50,[188][189][190] The oxide inclusions of this scale were not deleterious to the pitting corrosion resistance. 191,192 However, no MnS inclusions or large (Al, Ca)-oxide precipitates have yet been observed in the SLMed 316L stainless steel, which should be attributed to the extremely high solidification rate during the SLM process, however, there was enough time for the element diffusion (such as Mn and S) to form those inclusions during the traditional casting process.…”
Section: Al-based Alloysmentioning
confidence: 82%
“…10b, c, which was also confirmed by other reports. 50,[188][189][190] The oxide inclusions of this scale were not deleterious to the pitting corrosion resistance. 191,192 However, no MnS inclusions or large (Al, Ca)-oxide precipitates have yet been observed in the SLMed 316L stainless steel, which should be attributed to the extremely high solidification rate during the SLM process, however, there was enough time for the element diffusion (such as Mn and S) to form those inclusions during the traditional casting process.…”
Section: Al-based Alloysmentioning
confidence: 82%
“…When laser power was 150 W and scanning speed was 1400 mm s −1 , there was obvious corrosion product on the surface of the sample. Figure f shows that there was obvious oxygen enrichment near the manufacturing defect, and the corrosion product was more obviously detected by energy‐dispersive spectrometry due to its crevice‐like geometry …”
Section: Resultsmentioning
confidence: 99%
“…Manufacturing defects also have complex effects on pitting corrosion resistance and passivation film stability. Schaller et al showed that manufacturing defects in the selective laser‐melted 304 L stainless steel could result in a decrease in corrosion resistance in the solution with 5% HCl + 100 ppm FeCl 3 , which was attributed to the crevice‐like geometry of manufacturing defects . Manufacturing defects of the crevice‐like structure can significantly reduce pitting corrosion resistance of the sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review by Sander et al summarizes how some of these features can cause higher susceptibility toward the initiation of local corrosion than others and in relation to a wrought counterpart 17 . For instance internal part porosity, a common processing defect, has received significant attention and was shown to serve as preferential site for corrosion initiation in chloride solutions by several authors 7,9,[18][19][20][21][22] . Schaller et al and Melia et al empirically showed corrosion to preferentially occur at lack of fusion pores for powder-based AM austenitic stainless steels, leading to a reduction in breakdown potential (E b ) compared to areas excluding this porosity 7,20 .…”
Section: Introductionmentioning
confidence: 99%